Consumer choice behavior : a review of the history of economic thoughts on samuelson’s revealed preference theory and becker’s 1962 paper on irrational behavior. - Ghaibi, Sayed Elham (2023)
Programa de Pós-Graduação em Economia Aplicada. Departamento de Ciências Econômicas e Gerenciais, Instituto de Ciências Sociais Aplicadas, Universidade Federal de Ouro Preto.